A Critique of the Description and Emendation of the “Four Discourses” - انصاری جابری, جمال; محمدبیگی, شاهرخ (LANGUAGE ART, 2019)
Although the book Four Discourses is compact, it is a literally valuable work due to its authorʼs power in the two literary styles of simple prose and technical prose. In addition, the worthwhile information provided by this book about four professions of secretaryship, poetics, astronomy, and iatrology has added to the value of this book. Moreover, it is somehow considered a memorandum which should not be neglected. So, there is no doubt that understanding the beauties of the text of this literary treasure and enjoying it is dependent on the correct understanding of form and meaning of its text. Since after the wise emendation of the book Four Discourses by Allameh Mohammad Ghazvini, only professor Mohammad Moin has described this valuable work, and along with the description, he also has made some suggestions on the re-correction of some of its vocabularies; therefore, in this essay, it is tried to indicate some of the shortcomings of this single exposition. Subsequently, Moinʼs suggestions have been critically to present a more suitable and correct interpretation according to the text of the Four Discourses based on the in-text and out-text evidence as well as regarding the other related sources.